Accuracy of Portable Hardness Testers - Vasko, Alan; Sovik, Jan; Sedliackova, Zuzana (Manufacturing Technology Journal, 2019)
Hardness tests enable to determine one of the main mechanical properties of the material, namely hardness. For hardness testing, it is possible to use either conventional desk hardness testers or the currently increasingly used portable hardness testers. The paper is focused on determination of the accuracy and reliability of static (desk) and dynamic (portable) hardness testers. The paper deals with the measurement of hardness of calibration hardness plates by 4 different methods (Brinell, Vickers, Rockwell and Leeb) with using 5 different hardness testers (3 desk and 2 portable). The hardness values measured by the different hardness testers were compared to the reference hardness listed in the calibration hardness plates and consequently, the accuracy of these measurements was evaluated. The aim of the work has been to determine the accuracy and reliability of portable hardness testers in comparison with desk hardness testers.
Keywords: Hardness; Brinell; Vickers; Rockwell; Leeb